Taxonomy of the Oriental leafhopper genus Fistulatus (Hemiptera: Cicadellidae: Deltocephalinae), with description of a new species from China - Lu, Lin; Zhang, Yalin (Zootaxa, 2014)
A new species, Fistulatus quadrispinosus sp. nov. is described from the Qingliangfeng Mountains in Zhejiang Province in China. A key and checklist to species (males) of Fistulatus are also provided.